The correlation of severity of bronchiectasis based on modified reiff CT scoring with clinical outcomes - Rosli, Nur Salsabila Mohd (2018)
Objective: To determine the morphologic patterns of bronchiectasis and the correlation of disease severity based on Modified Reiff CT scoring among adult bronchiectasis patients with clinical outcomes. Methodology: Patients with positive HRCT thorax finding were traced retrospectively from the PACS system, Department of Radiology, HUSM. The inclusion criteria are patient aged 18 years old and above and confirmed cases of bronchiectasis by HRCT thorax scan. Each HRCT thorax image reviewed and scored using modified Reiff. Patient medical records reviewed and number of exacerbation and number of hospitalization related to the respiratory problem were calculated. Results: Total of patients are 90 (n=90) , with mean age of 57.97 years (45.6% male, 54.4% female). Types of bronchiectasis were tubular in 40%, varicose in 16.7%, cystic in 12.2% and mix types 31.1%. Disease severity assessment; number of exacerbation showed weak and positive relationship with modified Reiff score, p-value of 0.014. Number of hospitalization show no statistical significant with p-value of 0.189. Conclusions: In this study, morphological changes of bronchiectasis on HRCT thorax using modified Reiff may become predictor for the number of exacerbation but not a predictor for the number of hospitalization